Cortisol, high sensitivity C-reactive protein and ferritin adaptation to endurance training in naturally menstruating females vs. females using hormonal contraceptives - Kordrostami, Sarah (2024)
Introduction: Ferritin, hs-CRP and cortisol are markers of iron metabolism, inflammation and stress, respectively. The current longitudinal study investigated the effect of eight weeks of moderate-intensity aerobic exercise on cortisol, high-sensitivity C-reactive protein (hs-CRP), and ferritin among naturally menstruating females and hormonal contraceptive users.